Study of comparison of transvaginal cervical length and Bishop score in predicting successful labour induction- a prospective study from a tertiary care hospital of Rajasthan - Monika; Jakhar, Balveer; Choudhary, Neeraj; Khoiwal, Susheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Labor induction is one of the common interventions in obstetric practice. Assessment of cervix has been used as a predictor of the successful vaginal delivery. The traditional method of predicting whether an induced labour will result in successful vaginal delivery is based on the pre induction favourability of cervix as assessed by the Bishop score. Now we used transvaginal sonography (TVS) as an objective method of assessment of cervical length to evaluate the role of the pre-induction transvaginal ultrasonographic (TVS) cervical length in predicting labour outcome and comparing it to the Bishop score in patients undergoing induction of labour. Methods: This observational prospective study included 100 pregnant women in which induction of labour was performed at 37-42 weeks of gestation. Cervical length on transvaginal ultrasound and bishop score by digital examination is assessed prior to induction in cases according to standard protocol. Results: In our study though the sensitivity of the Bishop score in predicting the successful labour induction was higher (75.6%) compared with that of cervical length measured trans vaginally (69.35%). The specificity and positive predictive value for the cervical length (2.7 cm) was 77.78% and 91.49% compared with the Bishop score (4) 55.55% and 81.82% respectively. Conclusions: Bishop score and transvaginal cervical length both are good predictors of successful induction of labour. Transvaginal cervical length provides a better prediction of the likelihood of vaginal delivery within 24 hours of induction.